Parental trust and beliefs after the discovery of a six-year-long failure to vaccinate. Issue 2 (1st February 2021) - Brunelli, Laura; Valent, Francesca; Romanese, Federico; Tricarico, Pierfrancesco; Pellizzaro, Alice; d'Angelo, Matteo; Benetollo, Pier Paolo; Iob, Andrea; Forgiarini, Mariarita; Brusaferro, Silvio
ABSTRACT: Background: In Italy vaccine hesitancy worsened after a failure to vaccinate episode that took place in Friuli Venezia-Giulia Region until early 2017 which undermined herd immunity by leaving unprotected more than 5, 444 children. Methods: Between May and June 2017, 2, 557 parents were surveyed at the local vaccination clinic where they were invited within the subsequent extraordinary vaccination campaign. The aim of the survey was to evaluate whether the multi-channel extraordinary vaccination campaign had reached the target population and to know parental beliefs and trusted sources of information after the failure to vaccinate event. Results: While 279 parents were non-hesitant (10.9%) and 1, 491 hesitant acceptors (58.3%), just 38 (1.5%) refused to have their children revaccinated. Overall, the most consulted sources of information were print media (18.8%), physicians (16.0%), relatives and friends (12.1%). The majority of parents considered vaccination as a fundamental practice (73.9%), but many were worried about potential side effects (38.8%) or doubtful about the effectiveness of some vaccines (11.0%). According to parents, 19.7% of them (57) changed their opinion about vaccines after the Codroipo case. Conclusions: After the Codroipo case, most parents chose to have their children re-vaccinated and just a little proportion refused the re-administration of vaccines. More studies are needed to confirm the importance of a coherent multi-channel communication strategy using both traditional and new media in order to counteract vaccine hesitancy.